Resilience of Vocational Education and Training in Phases of External Shock - Experiences from the Corona Pandemic in Asian and European Skill Eco Systems - Evans, Karen; Ostendorf, Annette; Permpoonwiwat, Chompoonuh (innsbruck university press, 2023)
This anthology records research activities of the ASEM Research Network 2: Workplace learning. Right at the beginning of the pandemic, plans were made within the research network to examine this historically unique external shock in its impact on the systems of vocational skills production in the individual countries of the research network. All members were encouraged to closely follow the developments in the vocational education system already during the pandemic and to collect materials. For the scientific observations of the effects on the VET system of the respective countries, the so-called skill ecosystem perspective was used, which above all also establishes the connection of VET structures to the surrounding economic, legal, political, and social context. Specifically, the research questions focused on three aspects: how resilient the systems for development and assessment of vocational capabilities in the current and future workforce proved to be in the shock situation, which stabilising elements proved to be particularly helpful and which forced changes are still having an impact today. Finally, this research initiative has resulted in the contributions of this anthology, which refer to the skill ecosystems of Brunei, France, Germany, Latvia, Singapore, Thailand, England (and small islands in the British Isles), and Ukraine.